Prevention of mortality in acute lung injury induced by oleic acid: Application of polyherbal decoction (bronco T) - Mishra, Priyanka; Pandey, Ratna; Pandey, Nikhil; Tripathi, Suyash; Tripathi, Yamini Bhusan (Frontiers in Cell and Developmental Biology, 2022)
Acute lung injury (ALI) is a lethal respiratory disorder, directed towards uncontrolled inflammation, sloughing of alveoli, and altered cardiorespiratory parameters with a global mortality rate of 40%. This study was designed to assess the preventive effect of a polyherbal decoction (Bronco T, 1.5 g/kg b.w.) on cardiorespiratory variables in the oleic acid-induced ALI in rats. Oleic acid increases the level of neutrophil infiltration leading to pulmonary oedema and alters the cardiorespiratory dynamics. The adult male rats were surgically cannulated and treated with intravenous oleic acid (0.38 ml/kg b.w.) to establish the ALI model. Bronco T was pre-administered orally three hours before oleic acid. The biophysical, histological, biochemical, and molecular effects were compared with dexamethasone (5 mg/kg b.w. i.p.). Animals were randomly divided into control, lethal, standard and treatment groups. Respiratory frequency (RF), heart rate (HR) and mean arterial pressure (MAP) were recorded on a computerized chart recorder; arterial blood sample was collected to determine PaO2/FiO2, TNF-α, and MPO. Lipid peroxidation, superoxide dismutase, and catalase activity were evaluated to measure oxidative stress in bronchoalveolar lavage. Further, pulmonary water content, expression of COX-2 and histological examination was determined in the lung. A molecular docking study of the active phytoconstituent of BT obtained from HR-LCMS analysis against reported targets (IL-6, COX-2, TNFα, MPO and ENaC) of ALI was carried out. The B.T. pretreatment prevents mortality in comparison to the oleic acid group. It protects the lungs and heart from the detrimental effect of oleic acid at par with dexamethasone.COX-2 mRNA expression was significantly downregulated in the treatment group. The reduced level of TNF-α, MPO, SOD and catalase supported the protective effect of B.T. The in-silico study revealed strong binding interaction between the phytoconstituent (Galangin 3- [galactosyl-(1-4)-rhamnoside and Beta solamarine] of BT and the reported target. The B.T. pre-administration attenuates the oleic acid-induced mortality and cardiorespiratory toxicity.